The Uncertain Body: Lin Tianmiao's Mother Machine and Postsocialist Biopolitics. - Huang, Linda (Art Journal)
The article discusses the life, career, and accomplishments of Chinese mixed-media installation artist Lin Tianmiao. Topics explored include the possible influence of the population control policy in China on her artworks, the textile-weaving techniques she employed to depict maternal bodies and present themes such as reproduction and labor, and the details of her 2004 installation "Chatting," which featured naked female bodies.